The television world of Pushing daisies critical essays on the Bryan Fuller series - Burger, Alissa (McFarland & Co., Inc., Publishers, 2011)
"Pushing Daisies was one of the most successful network television shows in recent history. This collection of 10 essays addresses the off-beat elements that made the show a success. Divided into three sections, the essays address the themes of difference, placement of the series within a larger philosophical context and the role of gender on the show"--Provided by publisher.